2021
DOI: 10.1016/j.jksuci.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

SANA: Sentiment analysis on newspapers comments in Algeria

Abstract: a b s t r a c tIt is very current in today life to seek for tracking the people opinion from their interaction with occurring events. A very common way to do that is comments in articles published in newspapers web sites dealing with contemporary events. Sentiment analysis or opinion mining is an emergent field who's the purpose is finding the behind phenomenon masked in opinionated texts. We are interested in our work by comments in Algerian newspaper websites. For this end, two corpora were used; SANA and OC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 28 publications
0
17
1
2
Order By: Relevance
“…The best results obtained on SANA_Alg are up to 81.00% (for F1 score). This result outperforms the results presented in the research literature, where the F1 score presented by Rahab et al [29] was up to 75%. Hence, our approach and corpus lead to an improvement of 6% on this corpus.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The best results obtained on SANA_Alg are up to 81.00% (for F1 score). This result outperforms the results presented in the research literature, where the F1 score presented by Rahab et al [29] was up to 75%. Hence, our approach and corpus lead to an improvement of 6% on this corpus.…”
Section: Discussioncontrasting
confidence: 82%
“…The second one is PADIC corpus [28], which is a parallel corpus between MSA and many dialects, including DALG. The last one is SANA_Alg [29] that is a recent, an annotated sentiment corpus (which we are using for our experiments, to evaluate the proposed approach on a test corpus presented in the literature).…”
Section: Arab(ic+izi) Sentiment Analysis: Challengesmentioning
confidence: 99%
“…The annotation process was manually carried out via crowdsourcing using the CrowdFlower platform [28]. In [29], a sentiment corpus SANA for the Algerian dialect was collected from the web. The corpus contains 513 comments which are classified into positive or negative classes.…”
Section: Sentiment Annotationmentioning
confidence: 99%
“…Several studies suggested that sentiment analysis can be used to classify phenomenon in text data (Bringula et al, 2019;B. Liu, 2012;Miranda & Martin, 2020;Rahab et al, 2019;Ye et al, 2017).…”
Section: Analyses Of President's Speechesmentioning
confidence: 99%